2024
DOI: 10.1007/s10825-024-02134-z
|View full text |Cite
|
Sign up to set email alerts
|

A piezoelectric sensor with high accuracy and reduced measurement error

Zine Ghemari,
Salah Belkhiri,
Salah Saad

Abstract: In this work, the main focus is on studying the effects of piezoelectric materials and exploring the functionality of piezoelectric sensors. The physical behavior of the sensor is thoroughly examined and a mathematical formula relating the accuracy of the sensor to relative movement or vibratory displacement is derived. The developed model is veri ed through simulations and experimental tests. By carefully selecting the appropriate damping rate, it is possible to enhance the parameters of the piezoelectric sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Generally, these materials exhibit changes in mechanical, optical, and electrical characteristics. Among the various types of smart materials, piezoelectric materials are notable for exhibiting the piezoelectric effect [1][2][3][4], where their electrical properties change in response to pressure, and for possessing reversible characteristics known as the inverse piezoelectric effect [5][6][7][8], where the application or alteration of an electric field induces deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these materials exhibit changes in mechanical, optical, and electrical characteristics. Among the various types of smart materials, piezoelectric materials are notable for exhibiting the piezoelectric effect [1][2][3][4], where their electrical properties change in response to pressure, and for possessing reversible characteristics known as the inverse piezoelectric effect [5][6][7][8], where the application or alteration of an electric field induces deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric materials have traditionally been used to convert mechanical energy into electrical energy for applications, such as sensors, actuators, and transducers. , However, it is only recently that researchers have shifted focus toward using such materials for piezocatalytic water splitting. A significant milestone was marked by Hong et al, who demonstrated water splitting using piezoelectric ZnO microfibers and BaTiO 3 microdendrites .…”
Section: Introductionmentioning
confidence: 99%